A Hybrid Approach to Cloud Data Security Using ChaCha20 and ECDH for Secure Encryption and Key Exchange - Muhammed, Rebwar Khalid; Rashid , Zryan Najat; Saydah , Shaida Jumaah (Kurdistan Journal of Applied Research, 2025)
Cloud computing has transformed data storage and processing by offering on-demand resources and global accessibility. However, this convenience introduces significant security risks due to the reliance on third-party services, raising concerns about data confidentiality and integrity. This research proposes a hybrid encryption model that combines the high-speed ChaCha20 algorithm for data encryption with the Elliptic Curve Diffie-Hellman (ECDH) protocol for secure key exchange. The model ensures robust data protection in Cloud environments by generating a ChaCha20 key, encrypting it with ECDH, and securely storing encrypted key fragments in the cloud for later reassembly and decryption. This approach enhances security during data transmission and storage while mitigating the common vulnerabilities found in single-algorithm solutions. The study evaluates and compares the performance of ChaCha20 with ECDH against Rivest-Shamir-Adleman (RSA) with advanced encryption standard (AES) and Blowfish with Elliptic-Curve Cryptography (ECC). The results show that ChaCha20 with ECDH provides the fastest encryption time of 2ms and a key generation time of 15.8ms, with moderate memory usage. By contrast, RSA with AES is slower but offers consistent memory usage, while Blowfish with ECC balances speed and memory efficiency. The proposed hybrid model outperforms traditional encryption methods in both speed and security, making it suitable for modern cloud applications requiring scalability and high performance. Future research could focus on optimizing this model for resource-constrained environments, such as IoT and mobile.